Resveratrol, a food-derived polyphenol, promotes Melanosomal degradation in skin fibroblasts through coordinated activation of autophagy, lysosomal, and antioxidant pathways - Saki Okamoto; Saya Kakimaru; Mayuko Koreishi; Mika Sakamoto; Yoshimasa Nakamura; Hideya Ando; Yoshio Tsujino; Ayano Satoh (Journal of Functional Foods)
Resveratrol, a polyphenol found in grapes and peanuts, is known for diverse biological activities, yet its effects on dermal hyperpigmentation (so-called dark spots) remain unexplored. We investigated resveratrol's ability to enhance melanosomal degradation in human dermal fibroblasts. At concentrations of 25–50 μM, resveratrol increased autophagy as measured by microtubule-associated protein 1A/1B-light chain 3 (LC3)-II/LC3-I ratio and enhanced lysosomal activity as assessed by a lysosomal activity reporter system. RNA sequencing revealed upregulation of lysosomal and autophagy-related genes, including cathepsins. Furthermore, reporter assays showed resveratrol's activation of antioxidant response via nuclear factor erythroid 2-related factor 2 (NRF2)-mediated, leading to upregulation of transcription factor EB/transcription factor E3 (TFEB/TFE3), master regulators of lysosomal function. In fibroblasts pre-loaded with melanosomes, resveratrol reduced melanosome content compared to control by day 3. The findings reveal the activation of interconnected autophagy, lysosomal, and antioxidant pathways by resveratrol, suggesting potential applications in functional foods targeting dermal hyperpigmentation.